Innovating Restaurant Inventory Management Application Enhancing Quality And Efficiency Through Extreme Pro-gramming Approach - Sihombing, Denny Jean Cross (Jurnal Ekonomi, 2024)
This research investigates the complex challenges in inventory management within the restaurant industry, including the risk of inventory calculation errors, stock shortages, and material wastage. The Extreme Programming (XP) method is utilized to develop an inventory management application to address these issues. Through user requirement analysis, XP-based application development, and user evaluation stages, this study successfully designs and implements an efficient and adaptive application. User evaluation results indicate positive feedback, with 85% of users expressing satisfaction with the application, affirming that it provides optimal value by enhancing operational efficiency and improving restaurant customer experience. This research contributes to implementing the adaptive and responsive XP method to address changes in inventory management, proving its effectiveness in dealing with the complexities of the dynamic restaurant industry.